SUBSTANTIVE AND FUNCTIONAL CHARACTERISTICS OF LEGAL MEANS IN THE CONDITIONS OF TECHNOLOGIZATION OF PUBLIC LIFE (IN CONTINUATION OF THE IDEAS OF S. S. ALEKSEEV) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
The article presents a look at some prospects (the need) for the development of ideas about legal means proposed to the scientific community in S. S. Alekseev’s article ‘Legal means: problem statement, concept, classification’. It is pointed out the need for a theoretical and legal understanding of legal and technical regulation as a means of increasing the effectiveness of legal regulation.
Keywords: legal means; technologization; technical and legal norms